Resilience, Coping Strategies, and Stress Related to Online Diploma Exam in University Students in Poland - Byra, Stanisława; Boczkowska, Magdalena (Przegląd Badań Edukacyjnych (Educational Studies Review), 2022)
The present study investigated the association between resilience, coping strategies and stress related to online diploma exam under COVID-19 pandemic conditions. Sample of Polish university students (n = 453) in the last year of their bachelor’s or master’s completed a questionnaire containing questions about stress related to online diploma exam and experiencing difficulties related to studying online and scales: Questionnaire (KOP-26) by Gąsior, Chodkiewicz, Ciechowski, the Polish version of COPE by Wrześniewski, Sense of Stress Questionnaire (KPS) by Plopa and Makarowski. The results showed that higher resilience was associated with lower levels of online diploma exam stress, more frequent use of adaptive coping strategies and less frequent use of maladaptive coping strategies. Lower levels of online diploma exam stress were associated with more frequent use of coping strategies such as focus on the problem, humour and alcohol/drug ideation, and less frequent use of focus on/venting emotions. The relationship between resilience and online diploma exam stress was shown to be mediated by two coping strategies (focus on the problem and focus on/ venting of emotions). Generalized sense of stress was not a moderator of the mediating effect. The results of the study have shown that the relationship between resilience, coping strategies, online diploma exam stress and sense of stress was different in students who experienced online study difficulties and those who did not.